SERFONTEIN JH Correspondence - SERFONTEIN, JH (ARCA, 2018)
Correspondence inter alia with Tielman Roos, CR Swart, AJ Werth
COVERAGE: 1912-1949
Keywords: SERFONTEIN JH; Correspondence; Tielman Roos; CR Swart; AJ Werth